New emission line at ~3.5 keV - observational status, connection with radiatively decaying dark matter and directions for future studies - Iakubovskyi, D.A. (Advances in Astronomy and Space Physics, 2014)
Recent works of Bulbul et al. (2014) and Boyarsky et al. (2014), claiming the detection of the extra emission line with energy ∼3.5 keV in X-ray spectra of certain clusters of galaxies and nearby Andromeda galaxy, have raised a considerable interest in astrophysics and particle physics communities. A number of new observational studies
claim detection or non-detection of the extra line in X-ray spectra of various cosmic objects. In this review I summarise existing results of these studies, overview possible interpretations of the extra line, including intriguing connection with radiatively decaying dark matter, and show future directions achievable with existing and planned X-ray cosmic missions.